PENANGKARAN BENIH KENTANG BERMUTU SISTEM AEROPONIK DAN MEDIA STERIL DI DESA PANDANSARI KECAMATAN PAGUYANGAN KABUPATEN BREBES - Saparso Saparso; Khavid Faozi (Dinamika Journal : Pengabdian Masyarakat, 2019)
National seed systems still relying on the conventional production system and still need to increase the capacity of efficient seed potatoes technology to achieve independence seed producers in potato production centers. Empowerment of seed breeders through aeroponic technology is expected to increase the motivation of people in the implementation of the national potato seed technology innovation. Activities include training to enlighten the knowledge aspect of aeroponic technology innovation and national potato seed system. Making demonstration plots and aeroponic systems sterile media net home with intensive support can convince the public of the benefits of aeroponic technology for seed potatoes and potato agribusiness community. In general, the activities have been carried out according to plan with the physical performance of the activity by 100%, and the implementation of training activities and demonstration plots rewind time because farmers are not ready due to the busyness of the growing season as well as the financing of late. Seed potato training activities held on July 19, 2014, in the House of Mr. Warsono. Training materials presented include Aeroponic Technology in Potato Breeding, Seed Potato System National Potato Cultivation Technology Conservation and Production Systems Business Media sterile in Potato Quality. Through the training forum also gathered information on the seed and potato cultivation by farmers as well as to evaluate the implementation of the technology transfer to the questionnaire questions in the form of pre-test and post-test. Increasing knowledge about seed potato growers in aeroponics, and also increase its capacity as seed kentan. Seed potatoes (seeding) is aeroponics and seeding potato in sterile media has been practiced by farmers and plants grow normally. Farmers optimistic partners can perform independently seed potatoes after following the steps in training activities.